Photodynamic inactivation using a chlorin-based photosensitizer with blue or red-light irradiation against single-species biofilms related to periodontitis - Garcia de Carvalho, Gabriel [UNESP] (2020)
Chlorin-e6 (Ce6), as a photosensitizer (PS), has demonstrated significant reduction of microorganisms’ viability when irradiated by red light. However, the main absorption peak of this PS is located at blue light spectrum, which is less investigated. This study aimed to evaluate the effect of pure-chlorin-e6-mediated photodynamic inactivation (PDI) using different light sources (450 or 660 nm) against biofilms related to periodontitis. Streptococcus oralis, Fusobacterium nucleatum, Porphyromonas gingivalis, and Aggregatibacter actinomycetemcomitans single-species biofilms were developed under proper conditions for five days. PDI was performed using different concentrations of Ce6 (100 and 200 mM), wavelengths (450 and 660 nm) and comparisons were made after colony forming unit and confocal laser scanning microscopy (CLSM) analysis. The use of light and PS were also individually tested. The greatest bacterial elimination was observed in the group where PDI was employed with blue light and concentration of 200 mM for all bacterial strains tested (4.01 log10 for A. actinomycetemcomitans, and total elimination for P. gingivalis and S. oralis), except for F. nucleatum, where 3.46 log10 reduction was observed when red light and 200 mM Ce6 were applied (p < 0.05). The antimicrobial effects of PDI mediated by Ce6 for all single pathogenic biofilms were confirmed by live/dead staining under CLSM analysis. For all single-species biofilms, the use of PDI mediated by chlorin-e6 photosensitizer under blue or red-light irradiation (450 and 660 nm) demonstrated a significant reduction in bacterial viability, but blue light showed a promising higher photobiological effect, encouraging its adjuvant use to basic periodontitis treatment.